Analisis Representasi Visual Buku Teks Genetika Tentang DNA - Isnaeni, Bekti; Kuswandi, Paramita Cahyaningrum; Subiantoro, Agung Wijaya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the visual representation aspects and level of representation in genetics textbooks related to DNA material. This study is descriptive qualitative with two genetics textbooks as the research objects. The analysis technique used is visual representation function analysis and level of representation. The results of the analysis show that visual representation is dominated by illustrative functions (70-75%), followed by complementary functions (23-25%), while explanatory functions only appear 5%, and decorative functions are not found. The level of DNA topic representation falls under the molecular level of representation. This finding indicates that the visual representations in both genetics textbooks are predominantly illustrative, followed by complementary functions, while explanatory functions appear only to a limited extent, and decorative functions are absent. This analysis provides valuable insight into the quality of the textbooks and their relevance to potential student misconceptions. The implication of this study is that it can serve as a reference for authors of genetics textbooks, particularly in the topic of DNA, to pay closer attention to the balance of visual representation functions, ensuring that no single function dominates and that the visuals more effectively support students’ conceptual understanding.